2003
DOI: 10.1097/01.asn.0000037678.54984.41
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Allograft and Patient Survival in Type I Diabetic Recipients of Cadaveric Kidney Alone Versus Simultaneous Pancreas/Kidney Transplants

Abstract: Abstract. Simultaneous pancreas-kidney transplant (SPK) is now a common treatment for insulin-dependent diabetic patients with end-stage renal disease. Renal graft survival rates after SPK have been less well studied. This study compared the kidney survival results for 3642 SPK and 2374 cadaveric renal transplants (CRT) in type I diabetic patients at 112 US transplant centers reported to UNOS during 1994 through 1997. The analysis included follow-up information through September 2000. The kidney graft survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 12 publications
2
60
0
5
Order By: Relevance
“…The presence of an altered RI suggests a reduction of the intrarenal vascular surface and probably the appearance of glomerulosclerosis (5)(6)(7)(8). It is likely that abnormalities in RI and UAE appear earlier in the transplant kidney than in the diabetic patient's own kidney due to the "sensitizing" effect of calcineurin inhibitors on glomeruli.…”
Section: Preliminary Data On Nos Kidney Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of an altered RI suggests a reduction of the intrarenal vascular surface and probably the appearance of glomerulosclerosis (5)(6)(7)(8). It is likely that abnormalities in RI and UAE appear earlier in the transplant kidney than in the diabetic patient's own kidney due to the "sensitizing" effect of calcineurin inhibitors on glomeruli.…”
Section: Preliminary Data On Nos Kidney Expressionmentioning
confidence: 99%
“…Glomerular hyperfiltration is the first feature of renal involvement and can be observed soon after diabetes onset, accompanied by a loss of renal functional reserve (3). Microalbuminuria appears later, as do morphological changes such as thickening of the glomerular basement membrane and mesangial expansion (4).Nephrosclerosis or glomerulosclerosis of the transplanted kidney in end-stage renal disease (ESRD) type 1 diabetic kidney transplant patients may result from the interaction of diabetes, hypertension, obesity, smoking, and dyslipidemia and from nephrotoxicity of certain immunosuppressive drugs (calcineurin inhibitors but not only) (5-6), leading to a reduction in the intrarenal vascular surface area and an increase in vascular resistance (7-10).Pancreas and islet transplantation can confer insulin independence in type 1 diabetic transplant patients, thus preventing the progression to diabetic nephropathy, improving graft survival, and ameliorating diabetic macro-/microangiopathy (6,(11)(12)(13)(14)(15)(16)(17). It is likely that islet transplant could ameliorate renal function through improved glycometabolic control and restoration of C-peptide secretion (14,18 -23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies comparing survival rates between SPK and KA recipients showed conflicting results (5)(6)(7)(8)(9)(10)(11). In some studies, more favorable donors were used for SPK and healthier recipients received SPKs (5,7,8,11).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, more favorable donors were used for SPK and healthier recipients received SPKs (5,7,8,11). These studies relied on the multivariate analyses to adjust for recipient, donor, and transplant variables.…”
Section: Methodsmentioning
confidence: 99%